Continuous vs Intermittent Phototherapy in the Management of Non-Haemolytic Neonatal Hyperbilirubinemia - A Randomised Non - Inferiority Study - Patil, Mallanagouda M; S, Gowthami G; Bijapure, Hidaytullah R; Sajjan, Anil Kumar; Kalyanshettar, S S; Patil, S V (Journal of Nepal Paediatric Society, 2020)
Introduction: Phototherapy is used to manage neonatal hyperbilirubinemia in early life. We aimed to compare between intermittent and continuous phototherapy in reducing TSB, rate of fall of bilirubin, duration of phototherapy and duration of hospitalisation in neonates with non-haemolytic hyperbilirubinemia. Methods: Total 190 neonates who were > 34 weeks and birth weight ≥ 2000 gm were included. They were randomised into group A (continuous phototherapy) and group B (intermittent phototherapy). Group A received phototherapy for three hours and 45 minutes off and group B received phototherapy for three hours and then three hours off. TSB levels estimation were done in both groups and compared after each 12 hours, 24 hours, and 48 hours of commencing phototherapy. Results: The mean TSB at presentation was 15.64 ± 2.19 mg/dl for continuous and 15.03 ± 1.07 mg/dl for intermittent group. Mean TSB at 12, 24, 48 hours were 13.26 ± 2.4 mg/dl, 10.8 ± 1.72 mg/dl, 10.16 ± 0.95 mg/dl respectively for continuous and 12.6 ± 1.65 mg/dl, 10.04 ±1.8 mg/dl, 9.1 ± 0.66 mg/dl respectively for intermittent group (p < 0.05). The mean rate of fall in serum bilirubin was 0.22 ± 0.12 mg/dl/hr for group A and 0.21 ± 0.08 mg/dl/hr for group B (p = 0.45). There was not much difference in mean duration of hospitalisation in both groups (p = 0.547). Conclusions: Intermittent phototherapy is a non-inferior option to continuous phototherapy, in the management of non-haemolytic hyperbilirubinemia with additional advantages of less interrupted mother infant bonding and decreased irradiance.